Mask-related adverse skin reactions and risk factors: A literature review - Jin-Ling Ku; Min-Hao Sun; Yi-Chang Yen; Ching-Chi Chi (Wolters Kluwer Medknow Publications, 2023)
Wearing facial masks is a commonly used personal protection measure during the COVID-19 pandemic. However, prolonged use of masks has caused adverse skin reactions in both health-care workers (HCWs) and the public. In this study, we conducted a narrative review of mask-related adverse skin reactions and risk factors. Common mask-related adverse skin reactions include retroauricular dermatitis, cheilitis, rosacea, acne vulgaris, nasal bridge damage, itch, allergic contact dermatitis, and irritant contact dermatitis. Urticaria, facial pigmentation, and maceration were also reported as mask-related adverse skin reactions while the association was rarely reported. Long duration of wearing masks, preexisting skin diseases, and being HCWs are highlighted as definite risk factors. Skin conditions for example oily, dry, and sensitive skin lead to an increased risk of mask-related adverse skin reactions. In conclusion, this review provides a summary of mask-related dermatoses and their prevalence and risk factors. This article can inform the HCWs and the public to better identify mask-related adverse skin reactions and risk factors. Thus, they may adopt appropriate preventative measures based on their individualized circumstances.